Hypoglycemic activity of brown seaweed (Sargassum plagiophyllum) kombucha bioactive compound in rat model type-2 of diabetes - Priambodo Ahmad Faris; Martati Erryana; Firdaus Muhamad (BIO Web of Conferences)
Hyperglycemia is a condition of increased blood glucose with out of normal limits criteria associated with diabetes mellitus. Uncontrolled hyperglycemia is one of the causes of complications in diabetes mellitus sufferers. Sargassum plagiophyllum is one of brown seaweed that contains many bioactive compounds which are useful as hypoglycemic agents. The kombucha fermentation method is used to reduce structural complexity, thereby increasing the bioavailability of bioactives. This study aims to evaluate the administration of S. plagiophyllum kombucha (SK) to the blood profile of type 2 diabetes mellitus (DM2) rats treated with a 21% highfructose diet (HFD) with normal feed. S. plagiophyllum was obtained from Talango, Sumenep, Madura Island, East Java Province. 2-month-old male Rattus norvegicus was used as a model animal. The study consisted of 5 groups, including negative control, positive control (DM2), DM2 + SK 1.5 mL/250 g bw once a day, DM2 + SK 1.5 mL/250 g bw twice a day, and DM2 + SK 1, 5 mL/250 g bw three times a day. Animal model research was carried out for 2 months. The study’s conclusion shows that S. plagiophyllum kombucha has bioactive compounds as hypoglycemic agents and contributes to improving body weight, fasting blood glucose (FBG), lipid profiles, insulin, and MDA in type-2 diabetes rats model.